PEMBERIAN ASIMILASI NARAPIDANA RESIDIVIS (STUDI KASUS DI L.P. PEREMPUAN KELAS IIA MALANG) (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2020)
The policy of assimilation of prisoners in the midst of the COVID-19 pandemic, namely the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia Number 10 of 2020 concerning Conditions for Providing Assimilation and Integration for Prisoners and Children in the Framework of Prevention and Countermeasures of the Spread of COVID-19 is very interesting to be further peeled. The policy received a lot of support as well as criticism from many parties. Many people worry about the repetition of crimes committed by ex-assimilation prisoners. Based on the background above, the author raised the formulation of the problem as follows: